Waves and wave forces on coastal and ocean structures - Hudspeth, Robert T. (World Scientific, 2006)
This work focuses on: the physics of the fundamental dynamics of fluids and of semi-immersed Lagrangian solid bodies that are responding to wave-induced loads; the scaling of dimensional equations and boundary value problems, in order to determine a small dimensionless parameter - say, e - that may be used to linearize the equations and the boundary value problems so as to obtain a linear system; the replacement of differential and integral calculus with algebraic equations that require only algebraic substitutions instead of differentiations and integrations; and the importance of comparing numerical and analytical computations with data from laboratories and/or nature.
Keywords: Water waves -- Mathematical models.; Fluid dynamics -- Mathematical models.; Ocean waves -- Mathematical models.; elektronické knihy; electronic books